1964
DOI: 10.1021/ba-1964-0043.ch025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polar-Nonpolar Additives on Oil Spreading on Solids, with Applications to Nonspreading Oils

Abstract: Nonspreading oils can be prepared from many lubricating oils by proper choice of an adsorbable additive, but an additive that makes one oil nonspreading may cause violent spreading of another. This anomalous spreading is produced by surface tension gradients resulting from adsorptive depletion of additive along the edge of the drop. Oily contamination of a surface may also cause spreading of an otherwise nonspreading oil. Since contamination rarely produces a critical surface tension above 30 dynes per cm., a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…In the spreading tests of hexadecane blends on Si surfaces, four types of behaviours were observed, similar to those described by Cottington et al [41] for stainless steel surfaces:…”
Section: Spreading Tests Of Additive Solutionssupporting
confidence: 79%
See 2 more Smart Citations
“…In the spreading tests of hexadecane blends on Si surfaces, four types of behaviours were observed, similar to those described by Cottington et al [41] for stainless steel surfaces:…”
Section: Spreading Tests Of Additive Solutionssupporting
confidence: 79%
“…It was suggested that a difference in surface tension may also play a role in this type of spreading (i.e. by the Marangoni effect) [41,43]; however, as outlined above, the additives used in this study have negligible effect on surface tension. Although remarkable, this reactive spreading is highly impractical in terms of lubricant containment and was not further pursued in this study.…”
Section: Spreading Tests Of Additive Solutionsmentioning
confidence: 75%
See 1 more Smart Citation
“…we combine the evolution equations for the film thickness profile (11) and the field of adsorbate coverage (12) with the reaction term (14) and the disjoining pressure (13).…”
Section: Results For Model I (Only Adsorption)mentioning
confidence: 99%
“…Such motion of evaporating droplets has conventionally been explained by the vapormediated Marangoni effect [3][4][5][6][7]. Liquid vapor evaporating from one droplet condenses in other droplets and changes the local composition of the droplet (see Fig.…”
mentioning
confidence: 99%